Necrotizing Faciitis after Shoulder Mobilization and Intra-Articular Infiltration with Betametasone - Bento-Rodrigues, Joana (2013)
Necrotizing Fasciitis is a rapidly progressive, potentially fatal infection of superficial fasciae and subcutaneous tissue, usually resulting from an inciting trauma to the skin. Medical literature refers few cases of necrotizing fasciitis related to intra-articular infiltrations, that often lead to patients death. This report describes the clinical events on a 55 year-old diabetic patient who developed upper extremity Necrotizing Fasciitis, 18 days after shoulder mobilization and intra-articular infiltration, due to Staphylococcus epidermidis. An early surgical debridement was performed and antibiotherapy was established, resulting in a successful outcome, despite the functional disability. We point out, through this case, the possibility of intra-articular injections of drugs causing Necrotizing Fasciitis, especially in risk patients.